2009
DOI: 10.2478/v10033-009-0005-4
|View full text |Cite
|
Sign up to set email alerts
|

Controlling in Transition Environments: Empirical Evidence from Croatia

Abstract: Companies from formerly planned economies started to compete in the open market by the end of the 1980s and at the beginning of 1990s when transition processes began. This paper analyzes the controlling developments in specific circumstances of a transitional economy like Croatian, after almost two decades of transition. The study used the most successful Croatian companies as its sample. Also, we explored the controlling implementation in SMEs, the group of enterprises that make up 98% of business entities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…The controlling department is independently organized in most of the successful companies but it still does not exceed 50 per cent from estimated companies. (Špac & Mošnja-Škare, 2009), Previous research (Vitezić, 2006) and this research by interview method showed that controlling department is usually centrally organized in the large and medium companies and employs three to five people. It is mainly focused on financial aspect of the business and therefore uses financial indicators and some other quantitative indicators.…”
Section: Methodology and Research Resultsmentioning
confidence: 84%
“…The controlling department is independently organized in most of the successful companies but it still does not exceed 50 per cent from estimated companies. (Špac & Mošnja-Škare, 2009), Previous research (Vitezić, 2006) and this research by interview method showed that controlling department is usually centrally organized in the large and medium companies and employs three to five people. It is mainly focused on financial aspect of the business and therefore uses financial indicators and some other quantitative indicators.…”
Section: Methodology and Research Resultsmentioning
confidence: 84%
“…Introduction of such system could be a determining factor ensuring company's success. Studies conducted by many authors (Špac, Mašnja-Škare, 2009;Papp, Pajrok, 2010;Śliwczyński, 2011;Sestanj-Peric, Kukec, 2012;Bieńkowska, Zgrzywa-Ziemak, 2014;Vuko, Ovjan, 2013;Dobroszek, 2015;Perović et al, 2016;Todorović-Dudić et al, 2017 etc. ) confirm that introducing a controlling system helps to improve the functionality of companies and the process of decision making as well as to increase the company's value growth.…”
Section: Introductionmentioning
confidence: 99%
“…Z prieskumu v chorvátskych podnikoch vyplýva, že implementácia sa zvyšuje, keď sa majitelia nepodieľajú na manažmente, ale aj ak rastie veľkosť podniku. Okrem toho sa prieskumom preukázalo aj efektívnejšie využívanie účtovných informácií (Spac et al 2009).…”
Section: Controlling Controllingový Repoting a Význam Pre Riadenieunclassified